(untitled) (Applied Biological Research, 2016)
A field trial was conducted during kharif 2012 and 2013 to assess the fficacy of seven treatment-schedules against Epilachna beetle on brinjal. The application of neem cake @ 300 kg ha-1 before seedling transplantation and foliar sprays of chlorpyriphos 20 EC + cypermethrin 5 EC @ 0.15%, cartap hydrochloride 50 SP @ 0.1% and azadirachtin 1 EC @ 0.1% at 30, 50 and 70 days after transplantation (DAT), respectively [T1], proved most effective in reducing Epilachna population (73.9-74.7%). This was followed by treatment-schedule of seedling treatment with carbosulfan 25 EC @ 0.2% and foliar sprays of thiamethoxam 25 WG @ 0.1%, endosulfan 35EC @ 0.2% and Bacillus thuringiensis var. kurstaki 5 WP @ 0.2% at 30, 60 and 80 DAT, respectively [T4], which depicted 58.6-68.8% decrease in beetle population. Highest yield of 13.89 to 14.28 t ha-1 was obtained in T1 and lowest of 10.74 to 10.87 t ha-1 in T5 (seedling treatment with imidacloprid 17.8 SL @ 0.03% and foliar spray of imidacloprid 17.8 SL @ 0.02%, novaluron 10 EC @ 0.075%, B. thuringiensis var. kurstaki 5 WP @ 0.2% and novaluron 10 EC @ 0.075% at 30, 50, 70 and 90 DAT, respectively) by untreated control. The cost-benefit ratio was maximum in T3 (spray fipronil, novaluron, deltamethrin and fenvalerate at 30, 50, 70 and 90 DAT, respectively) and minimum in T6 (spray with thiamethoxam 25 WG @ 0.1%, spinosad 2.5 EC @ 0.03% and abamectin 1.9 EC @ 0.2% at 30, 50 and 70 DAT, respectively).